Guidelines for the Neurocritical Care Management of Aneurysmal Subarachnoid Hemorrhage - Treggiari, Miriam M.; Rabinstein, Alejandro A.; Busl, Katharina M.; Caylor, Meghan M.; Citerio, Giuseppe; Deem, Steven; Diringer, Michael; Fox, Elizabeth; Livesay, Sarah; Sheth, Kevin N.; Suarez, Jose I.; Tjoumakaris, Stavropoula (Neurocritical care, 2023)
Background The neurointensive care management of patients with aneurysmal subarachnoid hemorrhage (aSAH) is one of the most critical components contributing to short-term and long-term patient outcomes. Previous recommendations for the medical management of aSAH comprehensively summarized the evidence based on consensus conference held in 2011. In this report, we provide updated recommendations based on appraisal of the literature using the Grading of Recommendations Assessment, Development, and Evaluation methodology. Methods The Population/Intervention/Comparator/Outcome (PICO) questions relevant to the medical management of aSAH were prioritized by consensus from the panel members. The panel used a custom-designed survey instrument to prioritize clinically relevant outcomes specific to each PICO question. To be included, the study design qualifying criteria were as follows: prospective randomized controlled trials (RCTs), prospective or retrospective observational studies, case–control studies, case series with a sample larger than 20 patients, meta-analyses, restricted to human study participants. Panel members first screened titles and abstracts, and subsequently full text review of selected reports. Data were abstracted in duplicate from reports meeting inclusion criteria. Panelists used the Grading of Recommendations Assessment, Development, and Evaluation Risk of Bias tool for assessment of RCTs and the “Risk of Bias In Nonrandomized Studies – of Interventions” tool for assessment of observational studies. The summary of the evidence for each PICO was presented to the full panel, and then the panel voted on the recommendations. Results The initial search retrieved 15,107 unique publications, and 74 were included for data abstraction. Several RCTs were conducted to test pharmacological interventions, and we found that the quality of evidence for nonpharmacological questions was consistently poor. Five PICO questions were supported by strong recommendations, one PICO question was supported by conditional recommendations, and six PICO questions did not have sufficient evidence to provide a recommendation. Conclusions These guidelines provide recommendations for or against interventions proven to be effective, ineffective, or harmful in the medical management of patients with aSAH based on a rigorous review of the available literature. They also serve to highlight gaps in knowledge that should guide future research priorities. Despite improvements in the outcomes of patients with aSAH over time, many important clinical questions remain unanswered.